A evasão discente em tempos de pandemia (2020- 2022) nos cursos de graduação (bacharelado) do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba-Campus I - João Pessoa - Trindade, Cláudia Marcele Vieira (2024)
Student Dropout is a reality present in all Brazilian educational institutions. Dropout rates are high at all levels and modalities of education. Faced with the individual, social, institutional and economic impacts of this phenomenon, educational and control institutions are making efforts to control dropout. Previous studies have found that dropouts in the Federal Institutes of Education, Science and Technology reach the various modalities of education, in different degrees, and it is believed that due to the occurrence of the COVID-19 pandemic, this situation has worsened. In view of the above, this study aims to analyze the student dropout from undergraduate courses (bachelor’s degree), of the face-to-face modality, of the Federal Institute of Education, Science and Technology of Paraiba - Campus I- João Pessoa, in the period of the pandemic (2020- 2022). Regarding the methodology, the present study is classified as exploratory-descriptive research, with a qualitative-quantitative approach and of an applied nature. As for the technical procedures, this is bibliographic research, through a case study. The data will be collected produced from the bibliographical references and the application of a questionnaire, applied to the research subjects online via Google Forms. After analyzing the data, it was found that the socioeconomic profile of students who dropped out of the undergraduate courses researched at IFPB, in the period from 2020 to 2022, is mostly composed of mostly male, residing in the municipality of João Pessoa-PB, age group between 20 and 25 years old, color of brown skin, single, has no children, only worked before joining the IFPB, currently works, lives with his family, has a family income of 1 to 2 minimum wages, parents have a low level of education (incomplete primary education), He attended primary and secondary education at a public school. The main motivational factors for student dropout were difficulty reconciling work and study, difficulty adapting to remote teaching, class schedule, personal reasons, distance from the educational institution, lack of identification with the course and socioeconomic conditions. As suggestions to minimize student dropout rates, participants highlighted improvements in student assistance actions, flexibility in class schedules and the use of more participatory and inclusive pedagogical practices. Finally, we conclude that student dropout is a multifactorial phenomenon, with causes ranging from personal reasons to institutional factors, and that the motivational factors highlighted by participants were intensified with the changes resulting from the COVID-19 pandemic, such as mandatory isolation social situation, the economic crisis and the need to work to help with family income, significantly impacting graduation abandonment. We also emphasize that the best way to minimize student dropout rates is through preventive intervention in students prone to abandoning the course.